Implementasi Sistem Informasi Slip Gaji Karyawan Berbasis Digital pada CV Mandiri Sukses Pratama - Ariansyah Maulana; Farizi Ilham; Bagus Mada Rizki Pemusa; Dimas Ananda (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Advances in information technology are driving organizations to improve the efficiency of data management, including the employee payroll process. Manually creating and distributing payslips often leads to calculation errors, delays, and wasted time. Therefore, in this internship, a Java-based payslip automation system was developed. The system features Excel data import, automatic payroll calculations, PDF payslip generation, and email delivery. The development results indicate that the system can accelerate the process of creating and distributing payslips and improve the accuracy and efficiency of payroll management. This system is expected to assist the administration department in managing the employee payroll process more effectively.